2010
DOI: 10.1007/s11104-010-0580-2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic response of ginsenosides in American ginseng to root fungal pathogens

Abstract: The existence of a complex relationship between soil microbes and ginsenoside contents in their host plants has been reported by previous studies. Here, we analyzed the interaction between the root pathogens and the ginsenoside content in the roots of American ginseng. Two fungal pathogen species were isolated from diseased American ginseng roots, and identified as Fusarium oxysporum (isolate C1) and Fusarium solani (isolate F19) by molecular sequencing analysis. To determine the effect of Fusarium-mediated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 38 publications
3
16
0
Order By: Relevance
“…Ginsenosides, the main bioactive ingredients of Panax plants, can be secreted into the rhizosphere soil by roots, exerting autotoxicity or promoting the growth of root pathogens (Jiao et al 2010;Lei et al 2010;Nicol et al 2003;Yang et al 2015). Here, we found that both exogenous root exudates of P. notoginseng and a mixture of Rg 1 , Rb 1 and Rd ginsenosides at the corresponding concentrations found in root exudates could drive a similar change in soil microbiota.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Ginsenosides, the main bioactive ingredients of Panax plants, can be secreted into the rhizosphere soil by roots, exerting autotoxicity or promoting the growth of root pathogens (Jiao et al 2010;Lei et al 2010;Nicol et al 2003;Yang et al 2015). Here, we found that both exogenous root exudates of P. notoginseng and a mixture of Rg 1 , Rb 1 and Rd ginsenosides at the corresponding concentrations found in root exudates could drive a similar change in soil microbiota.…”
Section: Discussionsupporting
confidence: 54%
“…Many studies have shown that triterpenoid saponins can act as phytoalexins by providing a chemical defense against fungal infections in oats and tomatoes (Turner 1956;Osbourn 1996). Like other saponins, ginsenosides can also serve as chemical defenses against the infection of pathogen at high concentrations (Jiao et al 2010). Moreover, ginsenosides could inhibit the growth of Trichoderma hamatum (Nicol et al 2003) and other non-host pathogens (Yang et al 2018b).…”
Section: Discussionmentioning
confidence: 99%
“…Ginsenosides are primary components of ginseng and play a multi-purpose ecological role. Like other saponins, ginsenosides are fungitoxic in plants and act as a host for chemical defenses at high concentrations [ 43 ]. In the rhizosphere, ginsenosides not only exert autotoxic effects on Sanqi ginseng plants, resulting in poor defense and growth, but also stimulate the growth of soil-borne pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…The crude ginseng saponin fraction isolated from American ginseng exhibited antifungal activity and ginsenosides isolated from African Combretaceae exerted antimicrobial activity . Rb1, but not Re or Rg1, rapidly accumulated in the roots of American ginseng upon infection with two fungi, Fusarium oxysporum and Fusarium solani , and effectively inhibited conidium germination of both Fusarium species; this implies that Rb1 functions as a chemical defense mechanism in American ginseng roots against pathogenic fungi …”
Section: Chemical Defense Role Of Ginsenosides In Plantsmentioning
confidence: 99%
“…39 Rb1, but not Re or Rg1, rapidly accumulated in the roots of American ginseng upon infection with two fungi, Fusarium oxysporum and Fusarium solani, and effectively inhibited conidium germination of both Fusarium species; this implies that Rb1 functions as a chemical defense mechanism in American ginseng roots against pathogenic fungi. 40 Ginsenosides may also interrupt the life cycle of insects by binding to the ecdysteroid receptor due to the structural similarities between ginsenosides and ecdysteroids, which are the insect molting and metamorphosis hormones. 41,42…”
Section: Chemical Defense Role Of Ginsenosides In Plantsmentioning
confidence: 99%